Manajemen Bimbingan dan Konseling di Sekolah Menengah Atas dan Sekolah Menengah Kejuruan - Dwikurnaningsih, Yari (Universitas Muria Kudus, 2018)
This study aimed to describe guidance and counseling management in Senior High School and Vocational School in Salatiga. The type of this study was a quantitative descriptive. The subjects of this research were 69 school counselor of Senior High and Vocational School in Salatiga. Data was collected by using questionnaire, and was analyzed in quantitative term by calculating the presentage of the range from 5 categories, namely: very good, good, average, poor, and very poor. The result of the study showed that, guidance and counseling program planning was categorized average with 65,22%, guidance and counseling program organizing was categorized good with 57,97%, guidance and counseling program implementation was categorized very good with 49,28%, and guidance and counseling program evaluation was categorized average with 73,91%. The result became the basis for providing a recommendation for school counselor in increasing the guidance and counseling program planning and evaluation.